Blockchain Framework for Secure IoT Operations in Military Applications: Integrating LoRaWAN and Helium Network - S, Jebarani Evangeline; Arunachalam, Krishna Prakash; V, Seethalakshmi; A, Senthil Kumar; C, Reeda Lenus; R, Saranya (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The traditional IoT is typically based on centralized systems that are susceptible to multiple cyberattacks and a single point of failure. Modern industries regularly embrace block chain technology due to its decentralization and security. This study suggests a block chain-based system that guarantees reliable and secure operations. They suggest a secure compact block chain for handling access to precious information through instruments and controllers. Based on realistic military applications, the current investigation makes evidence for the benefits of merging LoRaWAN and Helium Network technology, and also demonstrates how deliberate research and analysis can bridge the block chain gap for military cyber defense. To improve the proposed system's computing efficiency, the block chain network has devised a rapid and power-saving decision technique for proof of authentication. The suggested framework for smart industrial environments has survived extensive testing and study to be sustainable. Use the suggested configuration to convert a standard processing system into an intelligent and secure industrial platform. This article aims towards assessing the practicality of Proof of Authority in the block chains network as a consensus algorithm. There are numerous techniques available for creating a consensus among the nodes.